Sistem Pakan Ikan Otomatis Berdasarkan Kualitas Air Menggunakan Metode Fuzzy Mamdani - Kurniawan, Rizki Fajar; Ashari, Ahmad; Hujja, Roghib Muhammad (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2025)
In addressing the global food scarcity crisis associated with global warming, the development of the fisheries sector becomes crucial, particularly in Indonesia. This research discusses the innovation of an automatic fish feeding system based on water quality detection using fuzzy logic control. The system integrates sensors for temperature, pH, and TDS to measure the conditions of fish pond water. Fuzzy logic control is employed to regulate the intensity of fish feeding based on environmental conditions. The system's performance is tested by comparing the fuzzy results from Matlab simulation with the implementation on Arduino. Despite differences, the results show a high level of consistency between the two systems. However, field trials reveal result variations, emphasizing the challenges of dealing with unpredictably changing environmental conditions. The conclusion highlights the disparities between simulation and field implementation, underscoring the importance of adjustments and calibration in practical applications.